Penguatan Dasar-Dasar Agama Hindu Melalui Kegiatan Basarah di Desa Parit Kecamatan Cempaga Hulu Kabupaten Kotawaringin Timur - Puspo Renan Joyo; Kunti Ayu Vedanti; Tiwi Etika; I Gede Arya Juni Arta; Susi Susi; Rupiadi Rupiadi (Jurnal Pengabdian Masyarakat Waradin, 2026)
The Kaharingan Hindu community represents an indigenous Dayak group residing in Central Kalimantan, distributed across fourteen districts and municipalities. One of these communities is located in Parit Village, Cempaga Hulu Subdistrict, East Kotawaringin Regency. Following its integration into Hinduism in 1980, various forms of religious guidance have been implemented; however, these efforts have not been fully optimal due to the vast geographical conditions of Central Kalimantan. This community service program conducted in Parit Village aims to strengthen the community’s śraddhā (faith) and jñāna (knowledge and understanding) of Hindu teachings. The program employed an outreach and educational approach focused on reinforcing the fundamental principles of Hinduism. Its implementation involved collaborative engagement with several partners, including the Ministry of Religious Affairs of the Republic of Indonesia (East Kotawaringin Office), the Kaharingan Hindu Council of Parit Village, and the active participation of the local Hindu community. The results indicate that many community members still lack comprehensive understanding of Hindu doctrines, partly due to limited access to sacred texts. Through the outreach activities, participants demonstrated improved comprehension of basic Hindu teachings, as evidenced by their ability to articulate and elaborate on the materials presented during the discussions.